Intrathecal injection of human umbilical cord blood stem cells attenuates spinal cord ischaemic compromise in rats†. (4th March 2014) - Judas, Gustavo Ieno; Ferreira, Sueli Gomes; Simas, Rafael; Sannomiya, Paulina; Benício, Anderson; da Silva, Luiz Fernando Ferraz; Moreira, Luiz Felipe Pinho
Abstract: OBECTIVES: Spinal cord ischaemia with resulting paraplegia remains a devastating and unpredictable complication after thoraco-abdominal aortic surgery. With the advent of stem cell therapy and its potential to induce nervous tissue regeneration processes, the interest in the use of these cells as a treatment for neurological disorders has increased. Human stem cells, derived from the umbilical cord, are one of the strong candidates used in cell therapy for spinal cord injury because of weak immunogenicity and ready availability. We sought to evaluate the use of human umbilical cord blood stem cells (HUCBSCs) to attenuate the neurological effects of spinal cord ischaemia induced by high thoracic aorta occlusion. METHODS: Forty Wistar rats were randomized to receive intrathecal injection of 10 µl phosphate buffered saline (PBS) solution containing 1 × 10 4 HUCBSCs, 30 min before (Tpre group: n = 10) and 30 min after (Tpos group: n = 10) descending thoracic aorta occlusion by intraluminal balloon during 12 min. Control groups received only PBS solution (Cpre group: n = 10; and Cpos group: n = 10). During a 28-day observational period, motor function was assessed by a functional grading scale (Basso, Beattie and Bresnahan). Segments of thoracolumbar spinal cord specimens were analysed for histological and immunohistochemical assessment for detection and quantification of human haematopoietic cells (CD45 + ) and apoptosis (transferase-mediated deoxyuridine triphosphate-biotin nick-end labelling). RESULTS: Overall mortality was 12 animals (30%). Therefore, the observational sample was composed of 28 animals. All groups showed similar incidence of paraplegia and mortality. The mean motor function scores showed no difference during time between the animals of each group, excepting for the Tpos group, which improved from 8.14 (±8.6) to 14.28 (±9.8) ( P < 0.01). A treatment-by-time interaction was detected among animals that received HUCBSCs 30 min after ischaemia, with BBB scores higher from Days 14 to 28 compared with the first observational day with statistical difference ( P = 0.01). Number of viable neurons was higher in the Tpos group ( P = 0.14) and the incidence of apoptosis was lower in the same animals ( P = 0.048), but showed no difference with its respective control. We confirmed the presence of CD45 + cells 4 weeks after intrathecal injection in both therapeutic groups but mainly in the Tpos group. CONCLUSIONS: Intrathecal transplantation of HUCBSCs is feasible, and it improved spinal cord function, when they were delivered 30 min after spinal cord ischaemia, in a model of endovascular descending thoracic aorta occlusion in rats. Human umbilical cord blood is one of the potentially useful sources of stem cells for therapy of spinal cord ischaemia.